Riebaline mase klasifikuojancios normatyvines lenteles sukurimas Lietuvos didelio meistriškumo ištverme ugdantiems sportininkams - Baranauskas, M.; Kupciunaite, I.; Lieponiene, J. (Sporto Mokslas-Sport Science, 2024)
The peculiarities of body composition can have a significant impact on athletes` physical potential as well as overall health status. Currently, there is still no universally adapted model for assessing athletes` body composition, and sports professionals often use different measurement methods and devices with certain limitations. The aim of the study was to measure the body composition of Lithuanian endurance male athletes using the bioelectrical impedance approach (BIA) as well as to create a normative table classifying the fat percentages. During the preparatory period, a quantitative single cross-sectional study was conducted. Lithuanian endurance male athletes (n = 89; 19.8 ± 1.8 years of age) were recruited to the quantitative single cross-sectional study. Based on the fat percentages of the male athletes we studied, according to the percentiles (P3, P10, P25, P50, P75, P90, P97) the benchmark percentiles for the classification of body fat percentage of professional male athletes competing in endurance sports through bioimpedanciometry were established. The established cut-off points may assist sports medicine professionals and sports dietitians in monitoring the adiposity endurance male sports athletes.